Heavy metals content in higher aquatic plants of the Northern Caspian Sea - Aset B. Imantaev; Nadezhda Y. Chesnokova (Водное хозяйство России: проблемы, технологии, управление)
Presence of certain microelements in higher aquatic vegetation enables to conclude on a water body pollution degree. Th is article analyzes the results of a study of the level of heavy metals content in the higher aquatic vegetation of the Northern Caspian Sea in 2018-2019.